ANGIOTENSIN II RECEPTOR ANTAGONISTS AND NEPHROPROTECTION: PLACE OF OLMESARTAN - V. V. Fomin (Кардиоваскулярная терапия и профилактика, 2013)
The paper presents the results of experimental studies and clinical trials which demonstrate nephroprotective effects of olmesartan.